CHINESE NEW ZEALANDERS’ PARTICIPATION IN LIFESTYLE POLITICS AND LIVED EXPERIENCE OF POWER - Yu Du (Journal of Social Political Sciences, 2023)
This paper explores how Chinese New Zealanders participate in lifestyle politics. It also uses Mark Haugaard’s four dimensions of power framework to explore how power operates when they participate in lifestyle politics. Based on an interpretive analysis of 38 Chinese New Zealanders’ in-depth interviews, I found that interviewees’ paths to and motivations for lifestyle politics varied. They constructed and disclosed unique political identities through their participation. Additionally, they all experienced the first, second, third, and fourth dimensions of power, even though they participated in lifestyle politics for various reasons. Their interpretations of power also varied. This study deepens the understanding of how power and politics are embedded in everyday life.